Strength, Stiffness, and Microstructure of Wood-Ash Stabilized Marine Clay - Abdullah Ekinci (Minerals, 2020)
The world’s population is growing at a rapid pace, thus increasing the need for shelter, which, because of increased carbon emissions, is making our planet less habitable. Thus, supplementary cementitious materials (SCMs) are used to reduce the embodied carbon emissions in the building sector. Wood-ash, as a replacement for cement in ground improvement, seems to be a promising material. In this study, we considered the strength, stiffness, and microstructural behavior of marine deposited clays of Cyprus treated with cement and wood-ash as a cement replacement. Since clay is abundant in nature, it could help stabilize waste to improve the mechanical behavior of produced composites. Portland cement (7%, 10%, and 13%) was replaced with various amount of wood-ash (5% and 10%) with two different dry densities (1400 and 1600 kg/m3) and three distinct curing periods (7, 28, and 60 days). Unconfined compressive strength (UCS), direct shear, porosity and pulse velocity tests were performed. Additionally, X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy analysis (EDX) were performed for microstructural evaluation of clay–wood-ash–cement mixtures. The results revealed that the replacement of cement with 5% of wood-ash yielded superior performance. The microstructure investigation of wood-ash–cement–clay blends further showed the formation of a densified matrix with stable bonds. Furthermore, the porosity and strength properties (unconfined compressive strength, splitting tensile strength, cohesion (C) and friction angle (ϕ)) of blends have unique relationships with porosity and binder contents, which were further confirmed by other supplementary materials and soils.